-4p-7=5p+2

Simple and best practice solution for -4p-7=5p+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4p-7=5p+2 equation:


Simplifying
-4p + -7 = 5p + 2

Reorder the terms:
-7 + -4p = 5p + 2

Reorder the terms:
-7 + -4p = 2 + 5p

Solving
-7 + -4p = 2 + 5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5p' to each side of the equation.
-7 + -4p + -5p = 2 + 5p + -5p

Combine like terms: -4p + -5p = -9p
-7 + -9p = 2 + 5p + -5p

Combine like terms: 5p + -5p = 0
-7 + -9p = 2 + 0
-7 + -9p = 2

Add '7' to each side of the equation.
-7 + 7 + -9p = 2 + 7

Combine like terms: -7 + 7 = 0
0 + -9p = 2 + 7
-9p = 2 + 7

Combine like terms: 2 + 7 = 9
-9p = 9

Divide each side by '-9'.
p = -1

Simplifying
p = -1

See similar equations:

| 5(x+5)-8=26-3x-9+8x | | 5.6a=.8(4-a) | | -2(5k-1)=-6(k+1) | | (3-2m)-(3m-2)= | | 25x+20y=220 | | 5xI+5=45 | | 1.6x=4.75 | | -2b-18+5b=-4 | | 3r-6=2r-2 | | 8(x-2)=12 | | 4(1-5x)+6=-26-8x | | 22-4x= | | 5(1+6n)-8(3n+3)=-67 | | 12r=R+1*8 | | 4(2*2+3)=-3(2-1)+31 | | -6+5(x-3)=14x+4-9x | | .33(9-6m)+.75(12m+8)= | | 10=-(n-5)-3(4n-6) | | -4x+-6=26 | | 3x^2+x^2=360 | | 38-4x=7x-6(6+8x) | | 0.3x-0.5(2x+3)=-0.8(x+2) | | -6x=3-21 | | 29+8v=-8(v-7)+7v | | 2x-x=4x+3 | | 2(2x-3)-2(2-3x)= | | X^2-81=o | | -8(0.1x+0.4)-1.9=-0.3 | | 2y-8=8x | | 3k-2x=t-5 | | -20+4+y=-6+16 | | -1=2p |

Equations solver categories